2009
DOI: 10.1143/jpsj.78.094706
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transition of Li2RuO3Induced by Molecular-Orbit Formation

Abstract: A pseudo honeycomb system Li 2 RuO 3 exhibits a second-order-like transition at temperature T=T c~5 40 K to a low-T nonmagnetic phase with a significant lattice distortion forming Ru-Ru pairs. For this system, we have calculated the band structure, using the generalized gradient approximation (GGA) in both the high-and low-T phases, and found that the results of the calculation can naturally explain the insulating behavior observed in the low-T phase. The detailed characters of the Ru 4d t 2g bands obtained by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 20 publications
(18 reference statements)
5
45
0
Order By: Relevance
“…Our calculations find rather small energy differences between ferro-and antiferromagnetic arrangement of the u ± spins, so when they are unbound and their covalent bond is broken at high temperature, they behave magnetically as nearly free spin 1/2 electrons. Indeed the difference between the experimental susceptibility at low temperatures (spin gap) and at high temperatures [7] is consistent with this scenario. Finally, (6) all investigated long range orders of the structural dimers are energetically strongly favorable when compared with the undimerized structure.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…Our calculations find rather small energy differences between ferro-and antiferromagnetic arrangement of the u ± spins, so when they are unbound and their covalent bond is broken at high temperature, they behave magnetically as nearly free spin 1/2 electrons. Indeed the difference between the experimental susceptibility at low temperatures (spin gap) and at high temperatures [7] is consistent with this scenario. Finally, (6) all investigated long range orders of the structural dimers are energetically strongly favorable when compared with the undimerized structure.…”
supporting
confidence: 76%
“…Finally, by analyzing the total density of states (DOS), we conclude that not only the orbital identified in Ref. 7 contributes to the covalency of the dimerized bond via direct overlap, but also another orbital provides an additional contribution via an O-assisted hopping. These findings play a very important role in understanding the microscopic physics of other 4d and 5d honeycomb oxides.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Nearly perfect hexagons of the high temperature C2/m phase undergo strong distortion, leading to a low temperature structure with significant shortening of one of the three inequivalent Ru-Ru bonds on each honeycomb 20 . Based on DFT calculations on the low and high temperature structures it was proposed that Li 2 RuO 3 undergoes a transition from a highly correlated metal to a molecular orbital insulator involving Ru-Ru dimerization and spin-singlet formation 20,21 . An alternative mechanism of spin-singlet formation driven by magnetoelastic coupling has also been proposed 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this dimer transition is accompanied by a strong decrease of the magnetization. In order to explain the origin of this transition, scenarios such as the transition from a highly correlated metal to a molecularorbital insulator accompanied by bond-dimer formation [20,22] and the formation of spinless dimers by magnetoelastic mechanism [23] have been proposed. More recently, a pair distribution function (PDF) analysis based on high-energy X-ray diffraction (XRD) revealed that the dimers exist even above T d but the positions of the dimers change dynamically [21].…”
Section: Introductionmentioning
confidence: 99%